Elucidating intermolecular forces to improve compatibility of kraft lignin in poly(lactic acid) - Esakkimuthu, Esakkiammal Sudha; Ponnuchamy, Veerapandian; Sipponen, Mika H.; DeVallance, David (Frontiers in Chemistry, 2024)
Owing to its abundant supply from renewable resources, lignin has emerged as a promising functional filler for the development of sustainable composite materials. However, achieving good interfacial compatibility between lignin and synthetic polymers, particularly poly(lactic acid) (PLA), remains a fundamental challenge. To advance the development of high-performance bio-based composites incorporating lignin and PLA, our study has scrutinized to unravel the nuances of interfacial binding interactions with the lignin and PLA composite system. Molecular level and experimental examinations were employed to decipher fundamental mechanisms governing and demonstrating the interfacial adhesion. We synthesized casted films of lignin/PLA and acetylated lignin/PLA at varying weight percentages of lignin (5%, 10%, and 20%) and comprehensively investigated their physicochemical and mechanical properties. The inclusion of acetylated lignin in the composites resulted in improved mechanical strength and Young's modulus, while the glass transition temperature and melting point were reduced compared to neat PLA. Systematic variations in these properties revealed distinct compatibility behaviors between unmodified lignin and acetylated lignin when incorporated into PLA.Molecular dynamics (MD) simulation results elucidated that the observed changes in material properties were primarily attributed to the acetylation of lignin. Acetylated lignin exhibited lower Coulombic interaction energy and higher van der Waals forces, indicating a stronger affinity to PLA and a reduced propensity for intermolecular aggregation compared to unmodified lignin. Our findings highlight the critical role of controlling intermolecular interactions and lignin aggregation to develop PLA composites with predictable performance for new applications, such as functional packaging materials.